Decolonising research methodologies: opportunity and caution. (September 2018) - Barnes, Brendon R
Decolonising methodologies attempt to bring together a number of critical, indigenous, liberation, and feminist methodologies to strengthen decolonisation research. Decolonising methodologies have potential, but it is important to be aware of possible limitations. I argue that the manner in which decolonising methodologies is located in the paradigm debate is limiting and prescriptive, lacks clarity of the concepts that it draws on, reproduces problematic representations of the marginalised, overemphasises how much choice researchers have in choosing decolonising methodologies, and does not address the systemic barriers to decolonisation scholarship. Recommendations for how to strengthen decolonising methodologies are presented.